PENGARUH KOMITMEN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR SEKRETARIAT DPRD PROVINSI ‘X’ - Puti Annisa Utari Puti Annisa Utari; Anna Marina Anna Marina (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2018)
The purpose of the study was to determine the effect of work commitment and work motivation on the performance of employees of the Provincial DPRD Secretariat 'X' partially and simultaneously at a 5% significance level. Population and research sample 96 people taken in total sampling. Data collection used observation and questionnaire techniques with a Likert score of 1 - 5. Data analysis used descriptive statistics and inferential statistics in the form of multiple linear regression. All instrument tests andclassical assumption tests are met before using multiple linear regression. Multiple linear regression equation Y = 26,131 + 0.036X1 + 0.536X2 + e. The research hypothesis is accepted partially and simultaneously. Correlation of work commitment and work motivation with performance 41.6% (low), coefficient of determination 17.3% and adjusted R square 15.6% means work commitment and work motivation can only explain theperformance of provincial DPRD Secretariat employees 'X' 15.6% while the remaining 84.4% is explained by other factors not included in the research model.